Bi2S3 nanoparticles anchored MWCNTs towards core-shell architecture: Counter electrode for dye-sensitized solar cell - Pooja A. Mithari; Avinash C. Mendhe; Sujata R. Patrikar; Chandrakant D. Lokhande; Babasaheb R. Sankapal (Applied Surface Science Advances, 2023)
A core-shell surface architecture has been developed through cost-effective and efficient sequential growth controlled chemical route, namely; successive ionic layer adsorption and reaction (SILAR) method to anchor Bi2S3 nanoparticles as shell over pre-coated MWCNTs as core to serve as a counter electrode (CE) in dye-sensitized solar cells (DSSCs) with eosin-Y dye loaded ZnO as photoanode, and polyiodide as liquid electrolyte. Electrochemical and device performance studies have been used to yield optimum growth through the number of SILAR cycles of Bi2S3 over MWCNTs. Electrochemical impedance spectroscopy (EIS) analysis revealed that, for well-optimized MWCNTs/Bi2S3 core-shell based device, the synergistic effect at the CE/electrolyte interface not only results in lower charge transfer resistance and faster electron transfer from CE to the electrolyte but equally doubled efficiency (0.343 %) than bare MWCNTs (0.162 %) and eight-fold enhanced efficiency than bare Bi2S3 (0.040 %).